Piraclostrobina nanoestruturada no controle de antracnose em pepino (Cucumis sativus) - Barzotto, Anderson (2019)
The control of pathogen populations in the field is becoming increasingly difficult, requiring that the number of pesticide applications increase or that the doses of the products are higher. In this way, the environmental risk and the quality of the food produced are questioned. Thus, producing food and controlling populations of pathogens requires a collective effort with interdisciplinary knowledge, and the application of nanotechnology to the agronomic area has shown good results. In this work, five nanostructures containing the fungicidal molecule pyraclostrobin were developed and characterized, and the in vitro and in vivo antifungal activity against the pathogen Colletotrichum lagenarium causal agent of anthracnose in cucumber (Cucumis sativus) was evaluated. In the in vitro bioassays the potentiation of the nanostructured fungicidal molecule was observed, believed to be due to the ease of access to the interior of the fungal cells promoted by nanoencapsulation. For even with the reduction of the concentration of the commercial product the control of the pathogen was obtained. In the in vivo bioassay the potentiation of the fungicidal molecule was again observed, as biological activity was observed using lower concentrations of the active principle. This was possibly due to the controlled release of the drug and the systemic action of nanostructured pyraclostrobin. In this way, it was possible to control the pathogen without causing plant phytotoxicity. Thus we conclude that with the application of nanotechnology to active ingredients it is possible to produce food using nanofungicide.